2022
DOI: 10.1371/journal.pone.0277424
|View full text |Cite
|
Sign up to set email alerts
|

What is important for people with type 2 diabetes? A focus group study to identify relevant aspects for Patient-Reported Outcome Measures in diabetes care

Abstract: Background Patient-Reported Outcome Measures (PROMs) aim to evaluate the quality of care based on the perspectives of patients rather than clinical indicators. Qualitative research is needed to identify these perspectives in people with type 2 diabetes. Objective To identify, for the first time in Israel, aspects valuable for people with type 2 diabetes that can be relevant for PROMs in diabetes care. Methods A qualitative study included three focus groups totalling 19 people with type 2 diabetes. Inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…What about the low-paid workers or the elderly who live off of their pensions, how could they pay for that? They cannot.” [ 34 ]. Another Israeli study showed that 10% of patients with diabetes were non-adherent with pharmacotherapy due to cost; and this behavior was associated with low socioeconomic position, unemployment, and lack of physician explanation about the prescribed medication [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…What about the low-paid workers or the elderly who live off of their pensions, how could they pay for that? They cannot.” [ 34 ]. Another Israeli study showed that 10% of patients with diabetes were non-adherent with pharmacotherapy due to cost; and this behavior was associated with low socioeconomic position, unemployment, and lack of physician explanation about the prescribed medication [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the results suggest that PROMs are applicable for routine measurement of diabetes quality care; the examined questionnaires are free for use in clinical practice, with acceptable length and are easily scored. Second, the examined PROMs were based on incorporating both the standard set recommended by ICHOM and aspects that are somewhat neglected in the existing PROMs, such as sexual dysfunction and financial burden, which were found valuable for patients with type 2 diabetes in our previous qualitative study [ 34 ]. Third, we used well-validated questionnaires and the combination of generic and diabetes-specific PROMs provided a comprehensive assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eigeland et al [ 36 ] reported that critical physician behaviors in the formation of a good physician-patient relationship can be grouped into six domains: (1) Valuing the whole person, (2) investigating and planning for the future, (3) collaboration and empowerment, (4) validation and emotional support, (5) politeness and courtesy, and (6) professionalism. Abdel-Rahman et al [ 37 ] proposed important domains for people with diabetes, including challenges living with diabetes; mental health issues, including depression, distress, anxiety, frustration, and loneliness; self-management ability; and patient-clinician relationships. Zeh et al [ 38 ] assessed PCC among patients with chronic diseases and proposed that PCC elements include the appropriate length of access to care, competence, empathy, individual consideration of each patient's situation, taking a holistic perspective of the patient, patient-centered communication, the integration of multidisciplinary treatment, transparency regarding waiting time and the reduction of unequal access to care.…”
Section: Introductionmentioning
confidence: 99%